Oxidation Resistance of NiCrAlY Coating Prepared by Arc Ion Plating - Bo YU; Xiao-peng CHANG (Medžiagotyra)
With the rapid development of the aviation industry, the working conditions of the aero-engines have become even worse. With a rise in inlet temperatures, the aero-engine blades are easily oxidized at high temperature, which consequently reduces their service life. MCrAlY coating (M refers to Fe, Ni, Co, etc.) has good high temperature oxidation resistance. It is considered to be an effective method to solve the problem of high temperature oxidation of aero-engines blades, and has gradually become the current domestic and foreign scholars focus. Arc ion plating is a mature technology for the preparation of MCrAlY coating, which has been paid much attention. Based on the arc ion plating process, and Ni-base superalloy GH4133 for aero-engines blades, coating the surface with NiCrAlY coating, after heat treatment, high temperature oxidation resistance test, at a constant temperature of 920 ℃, continuous oxidation test for 192 h, the micro-morphology, microstructure and oxidation process of the samples were analyzed by SEM, XRD, and EDS. The results: 1) NiCrAlY coating has a high density, there are many fine particles distributed on the surface of the coating, the surface is smooth, no micropores, pits and other defects, the coating and the matrix material formed a close bonding state; 2) after heat treatment, the particles on NiCrAlY coating surface are arranged more closely, the coating changed from NiAl phase to Ni3Al phase, which improved the high temperature oxidation resistance of the coating; 3) during the initial stage of high temperature oxidation, a uniform and dense protective layer of Cr2O3 was formed on the surface of the coating, which effectively prevented the oxygen from diffusing into the inner of the coating, thus greatly improving the anti-oxidation performance; 4) during the oxidation process, the interdiffusion of Cr occurs at the interface between the coating and the substrate, mainly in the form of Cr element diffusing from the coating to the substrate. When the oxide layer Cr2O3 cracks or peels off, a new oxide layer can be formed after the substrate contacts with oxygen, which decreases the rate of oxidation weight gain and continues to play the role of high temperature oxidation protection.